Social media addiction and its impact among the school students during COVID-19 lockdown in an urban area of Western India: a cross-sectional study - Engti, Raktim; Momin, Mohmmedirfan H.; Vyas, Shailee N. (International Journal of Research in Medical Sciences, 2022)
Background: Reports indicate significant increase in number of social media users. Teenagers are among the most prolific users of social media. Subsequently, questions and controversies emerge about its positive and negative effects, including their safety, academics and inter-personal relationships. This study will help in identifying teenagers at risk and implications of social media addiction on students. Methods: A cross sectional study conducted among school students of randomly selected schools of Surat city. Social media addiction scale-student form was used for data collection. Data entry in Microsoft excel and analysis was done by Epi-info. Univariate analysis was done to calculate mean and standard deviation while bivariate analysis for chi square test. Results: With 434 students of grade 9-12, mean age was 15.70±1.20 years. The prevalence of social media addiction was 23.5%. Girls were significantly associated with social media addiction. Overall, 26% of the students agreed that they were eager to go on social media, 14% of the students agreed that a life without social media becomes meaningless for them and 14.3% of the students agreed that they were unhappy when they are not on social media. Overall, 21.5% agreed that their productivity has decreased due to social media use and 12% had physical problems because of social media use. Conclusions: Risk factors for addiction were younger age group (13-15 years), female gender and students of standard 9. The academics was hampered for all the students irrespective of their age. There was a negative effect on their inter-personal relationships, mental and physical health.